Novel swine origin influenza a (H1N1) virus in humans - Merijanti, Lie T. (Universa Medicina, 2009)
In March and early April 2009, while much of the world was focusing on the threat of avian influenza originating in Asia, intelligence gathering systems were also extracting evidence of an epidemic of acute respiratory infections in Mexico and southern California. Although the exact sequence of events is uncertain, the Centers for Disease Control and Prevention (CDC) had confirmed the presence of a novel reassortment of Influenza A strain H1N1 from avian, swine, and human strains. On 25 April 2009, The World Health Organization (WHO) declared the swine flu outbreak in North America a public health emergency of international concern. On 29 April 2009, the International Health Regulations emergency committee recommended a change from WHO pandemic influenza phase 4 to phase 5. This means that WHO views a pandemic as imminent. WHO and the CDC have confirmed that the new swine flu virus is transmitted between humans.